Information System for Forex Investment and Their Effects on Investment Growth in Foreign Currencies - L Puspitawati; A K Ahmad (International Journal of Research and Applied Technology (INJURATECH), 2021)
This study aims to provide an overview of the growth of the foreign exchange (forex) industry and its prospects in Indonesia in the future, then provide a brief overview of how to start forex investment and what factors influence it and are inseparable from social, economic factors and politics that occur in a country. In fact, the current social, economic and political conditions in Indonesia are still unstable, and this will greatly affect the interests of students as potential investors to invest in forex. The method used in this research was qualitative descriptive method by conducting literature review from a variety of reliable reference. The results of this study indicated that potential investors in Indonesia had not yet fully gained adequate insights about forex investments that were of public welfare so that they were not yet interested in making forex investments. Other than that, potential investors were not sure that forex investment could be used as an alternative investment to improve prosperity.